Implementation of Congenital Hypothyroidism Screening Program at Community Health Center - Nasution, Ainun Budi; Reni Aprinawaty Sirait; Desideria Yosepha Ginting (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: The implementation of the Congenital Hypothyroidism Screening (SHK) program at UPTD Puskesmas Tebing Syahbandar has not yet achieved the target of screening 100% of newborns, with coverage rates of only 1.36% in 2023 and 15% in 2024. Several challenges hinder the program’s effectiveness, including limited resources and resistance from parents.Objective: This study aims to analyze the implementation of the SHK program at UPTD Puskesmas Tebing Syahbandar, identify the factors contributing to the low screening coverage, and propose recommendations for improving the program’s effectiveness and achieving the desired target. Research Method: A qualitative approach is used in this study, employing in-depth interviews with informants including healthcare workers, midwives, and the head of Puskesmas. The data collected was analyzed to identify key themes and factors affecting the program’s implementation. Results: The findings indicate that while the SHK program follows the guidelines set in Permenkes No. 78/2014, it faces significant barriers such as insufficient supply of screening materials (e.g., filter paper), limited training for healthcare personnel, and lack of comprehensive education for parents. These issues result in low participation rates and missed opportunities for early detection of congenital hypothyroidism. Conclusion: Addressing the challenges related to material availability, enhancing healthcare worker training, and improving communication and education for parents are essential to reaching the program’s target of 100% screening coverage.